Immunogenicity and safety of WHO-approved TRC-ID regimen with a chromatographically purified Vero cell rabies vaccine with or without rabies immunoglobulin in children - Piyada Angsuwatcharakon; Sumana Khomvilai; Kornvika Limsuwun; Natchaya Ratananpinit; Apinya Khamchat; Teeranit Sanitnai; Terapong Tantawichien (Taylor & Francis Group, 2018)
Introduction: Children are at risk of rabies exposure in many Asian countries. The safety and immunogenicity profile of the WHO-approved two-site intradermal Thai Red Cross regimen (modified TRC-ID regimen; 2-2-2-0-2) with a new chromatographically purified Vero-cell rabies vaccine (CPRV) is lacking. Area covered: We studied the safety and immunogenicity of the TRC-ID regimen with a new CPRV in non-immunized Thai children with possible or proven rabies exposure. Thirty-nine seronegative patients (age range 2-14 years) with rabies exposure (WHO categories II or III) received two 0.1-mL intradermal doses of CPRV at both deltoid regions on days 0, 3, 7, and 28. Twenty-five patients (64.1%) received rabies immunoglobulin due to having rabies exposure, according to WHO category III. All serum samples were tested for rabies neutralizing antibody (Nab) by the rapid fluorescent focus inhibition test (RFFIT) before vaccination, and on days 14 and 90 after vaccination. All patients had an adequate immune response (Nab titers ≥ 0.5 IU/mL) on days 14 and 90. No patients died of rabies infection. No serious adverse reactions were observed. Expert commentary: CPRV is economic, safe, and immunogenic if given as the modified TRC-ID regimen in children.